I am the cheese : a novel - Cormier, Robert (New York : Dell, 1983)
A young boy desperately tries to unlock his past yet knows he must hide those memories if he is to remain alive.
5.6
7-10
Senior High School Library Catalog (Wilson)
Junior High School Library Catalog (Wilson)
810
Keywords: Organized crime -- Fiction; Intelligence service -- Fiction; Organized crime -- Fiction; Intelligence service -- Fiction